Intelligent compress bin / Muhammad Nabil Nazmi Mohd Nadzir and Abdul Hadi Abdul Rahim @ Ibrahim - Mohd Nadzir, Muhammad Nabil Nazmi; Abdul Rahim @ Ibrahim, Abdul Hadi (School of Mechanical Engineering, 2023)
Every day, every restaurant produces garbage. The garbage is produced by the kitchen, dining room, and customers. However, available garbage bins cannot accommodate excessive amounts of garbage at one time. The bin needs to be emptied and the plastic bag needs to be changed and disposed of all the time. The objective of this project is to reduce the rate of changing and disposing of garbage by compressing the trash in the bin. Uncompressed garbage occupies a big amount of space in the bin. Compressing the garbage will prolong the time for the bin to be full of garbage, thus saving the usage of plastic bags. Furthermore, the compression process is hygienic because hands are not used to compress the garbage. The garbage compression is activated by pressing a button using a leg. This bin will be useful to all restaurants, cafes, and canteen